A Phase Ib Study of Sorafenib (BAY 43‐9006) in Patients with Kaposi Sarcoma. (24th March 2017) - Uldrick, Thomas S.; Gonçalves, Priscila H.; Wyvill, Kathleen M.; Peer, Cody J.; Bernstein, Wendy; Aleman, Karen; Polizzotto, Mark N.; Venzon, David; Steinberg, Seth M.; Marshall, Vickie; Whitby, Denise; Little, Richard F.; et al.
Abstract : Lessons Learned : Oral targeted agents are desirable for treatment of Kaposi sarcoma (KS); however, in patients with HIV, drug–drug interactions must be considered. In this study to treat KS, sorafenib was poorly tolerated at doses less than those approved by the U.S. Food and Drug Administration for hepatocellular carcinoma and other cancers, and showed only modest activity. Sorafenib's metabolism occurs via the CYP3A4 pathway, which is inhibited by ritonavir, a commonly used antiretroviral agent used by most patients in this study. Strong CYP3A4 inhibition by ritonavir may contribute to the observed sorafenib toxicity. Alternate antiretroviral agents without predicted interactions are preferred for co‐administration in patients with HIV and cancers for which sorafenib is indicated. Background: We conducted a phase Ib study of sorafenib, a vascular epithelial growth factor receptor (VEGFR), c‐kit, and platelet derived growth factor receptor (PDGFR)‐targeted treatment in Kaposi sarcoma (KS). We evaluated drug–drug interactions between sorafenib and ritonavir, an HIV medication with strong CYP3A4 inhibitory activity. Methods: Two cohorts were enrolled: HIV‐related KS on ritonavir (Cohort R) and HIV‐related or classical KS not receiving ritonavir (Cohort NR). Sorafenib dose level 1 in cohort R (R1) was 200 mg daily and 200 mg every 12 hours in cohort NR (NR1). Steady‐state pharmacokinetics were evaluated at cycle 1, day 8. KS responses and correlative factors were assessed. Results: Ten patients (nine HIV + ) were enrolled: R1 (eight), NR1 (two). Median CD4 + count (HIV + ) was 500 cells/µL. Dose‐limiting toxicities (DLTs) were grade 3 elevated lipase (R1), grade 4 thrombocytopenia (R1), and grade 3 hand‐foot syndrome (NR1). Two of seven evaluable patients had a partial response (PR; 29%; 95% CI 4%–71%). Steady‐state area under the curve of the dosing interval (AUCTAU ) of sorafenib was not significantly affected by ritonavir; however, a trend for decreased AUCTAU of the CYP3A4 metabolite sorafenib‐N‐oxide (3.8‐fold decrease; p  = .08) suggests other metabolites may be increased. Conclusion: Sorafenib was poorly tolerated, and anti‐KS activity was modest. Strong CYP3A4 inhibitors may contribute to sorafenib toxicity, and ritonavir has previously been shown to be a CYP3A4 inhibitor. Alternate antiretroviral agents without predicted interactions should be used when possible for concurrent administration with sorafenib.